Acidity and Charge Characteristics of Marine Alluvial Soils from Carey Islands, Selangor - Jusop, Shamsuddin; Paramananthan, S. (1988)
Six soil series from Carey Island were investigated to determine their acidity and charge characteristics. The study showed that the soils contained high amounts of basic cations, Al and S042-, which were reflected by their low pH and high electrical conductivity. The soils were highly buffered below pH 5.5 and this was found to be highly correlated to Al content. Further, it was found that negative charges on the clay surfaces increased with increase in soil pH. These observations' are contrary to the fact that the clay minerals in these soils are of the permanent charge type.